Implikasi Delik Penghinaan di Media Sosial terhadap Pemenuhan Hak atas Kebebasan Berekspresi - Fadil Ravi Rasad; Apriliani Kusumawati (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study employs a normative juridical method by examining legislation, court decisions, and relevant legal literature. The first finding shows that Article 27A of the Electronic Information and Transactions Law contains ambiguous elements that are inconsistent with constitutional guarantees of freedom of expression and the standards set under Article 19 of the ICCPR. The second finding demonstrates that limiting instruments such as the Joint Ministerial Decree (SKB), Constitutional Court decisions, and Anti-SLAPP regulations have not been fully effective in preventing misuse of defamation provisions in digital spaces. These findings underscore the need for normative harmonization to ensure balanced protection for reputation and freedom of expression.